Physics and mathematics of link homology: Séminaire de mathématiques supérieures Physics and Mathematics of Link Homology, June 24 - July 5, 2013, Centre de recherches mathématiques, Université de Montréal, Québec, Canada - Gukov, Sergei; Khovanov, Mikhail; Walcher, Johannes (Contemporary mathematics, 2016)
Chern-Simons theory and knot invariants / Ramadevi Pichai and Vivek Kumar Singh -- Tensor product algebras, Grassmannians and khovanov homology / Ben Webster -- Lectures on knot homology and quantum curves / Sergei Gukov and Ingmar Saberi -- An introduction to knot floer homology / Ciprian Manolescu -- Lectures on knot homology / Satoshi Nawata and Alexei Oblomkov